Case Report: Giant congenital transmesenteric hernia in a 6-month-old infant: a case of delayed recognition and critical diagnostic lessons - Fang, Xinggui; Wang, Benquan; Yang, Biao; Gao, Qun (Frontiers in Pediatrics, 2025)
Congenital transmesenteric hernia, a rare internal hernia, is notoriously challenging to diagnose preoperatively due to nonspecific symptoms and inconclusive routine evaluations. In infants, early manifestations such as vomiting, irritability, and diarrhea often mimic acute gastroenteritis, leading to delayed recognition. Without timely intervention, progression to intestinal strangulation, necrosis, and shock significantly escalates treatment complexity and mortality risk. We report a case of a 6-month-old female infant with approximately 131 cm of necrotic small bowel secondary to a giant transmesenteric hernia. This case illustrates the clinical trajectory, diagnostic pitfalls, and surgical management, highlighting the imperative for early suspicion and intervention. Critical analysis of this case underscores that prompt surgical correction is pivotal to mitigate morbidity and mortality in such scenarios. Enhanced clinician awareness of this condition and its subtle early signs could improve outcomes in pediatric patients.